2017
DOI: 10.1016/j.ajhg.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variant Ameliorates β-Thalassemia Severity by Epigenetic-Mediated Elevation of Human Fetal Hemoglobin Expression

Abstract: A delayed fetal-to-adult hemoglobin (Hb) switch ameliorates the severity of b-thalassemia and sickle cell disease. The molecular mechanism underlying the epigenetic dysregulation of the switch is unclear. To explore the potential cis-variants responsible for the Hb switching, we systematically analyzed an 80-kb region spanning the b-globin cluster using capture-based next-generation sequencing of 1142 Chinese b-thalassemia persons and identified 31 fetal hemoglobin (HbF)-associated haplotypes of the selected 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…However, we found the methylation patterns in γ-globin promoter showed difference between TFH and TFL group of β-thalassemia. The methylation level of most CpG sites in γ-globin promoter were hypomethylated, especially in + 17 and + 50 sites, in the BM tissues of TFH patients, compared with TFL patients, which was consistent with our previous report [12]. The γ-globin promoter methylation, not LCR region DNA methylation, might be the main effect to γ-globin expression, and the methylation alteration in the γ-globin promoter may be a driving factor leading to remote regulation between globin promoter and LCR regions [19].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, we found the methylation patterns in γ-globin promoter showed difference between TFH and TFL group of β-thalassemia. The methylation level of most CpG sites in γ-globin promoter were hypomethylated, especially in + 17 and + 50 sites, in the BM tissues of TFH patients, compared with TFL patients, which was consistent with our previous report [12]. The γ-globin promoter methylation, not LCR region DNA methylation, might be the main effect to γ-globin expression, and the methylation alteration in the γ-globin promoter may be a driving factor leading to remote regulation between globin promoter and LCR regions [19].…”
Section: Discussionsupporting
confidence: 93%
“…The hypomethylated patterns in globin promoters might make it easier to access for some transcription factors mediating the looping with globin promoter. In fact, our previous study showed that a SNP rs368698783 was associated with the methylation level on + 17 CpG site in γ-globin promoter [ 12 ], by recruiting DNMT3A to the promoter and further regulating the γ-globin expression, supporting the important role of γ-globin promoter methylation in regulation of γ-globin expression.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Specifically, HbF blocks HbS from dimerizing, thereby preventing hemoglobin polymer chaining and decreasing the probability of a vaso-occlusion [1,17]. Hydroxyurea, thalidomide, sodium butyrate, and decitabine, a DNMT1 targeting agent, have been previously shown to work through induction of HbF and subsequent protection against VOCs [5,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%